Climate change effect on Somalia’s pastoralists: Systematic review - Samatar, Elmi Hassan (Edelweiss Applied Science and Technology, 2024)
This paper offers the findings of a comprehensive review of the research literature on how pastoralists are being affected by climate change, what are the observed impacts of climate over the past few decades, how resilient are the pastoralists against climate change, and what are the predicted climate impacts in the coming decades. A total of 357 papers were properly screened based on research title and abstract. 156 papers were excluded as a result of the exclusion criteria (duplicates, studies not focused on climate, etc.), while 149 publications were before 2013. Finally, 52 papers qualified to be considered for review. Somalia has experienced above 30 climate-related shocks since the 1990s, including 19 floods and 12 severe droughts. Since 1991, Somalia has experienced a continuous increase of 10C to 1.50C in median annual temperatures. The average daily maximum temperature ranges from 300C to 400C and according to long-term predictions, temperatures will continue to rise by 3.20C to 4.30C by 2100. As per the findings, there are five basic adaptation techniques used by herders: transferring livestock to better grazing regions, adopting drought-resistant crops and livestock, planting early, and relocating to other settlements. Climate change has had substantial direct and indirect effects on Somalia’s pastoralists; water resources and pasture due to recurrent droughts and floods, which has increased the vulnerability of the pastoral communities. To address the above-highlighted impacts, purpose-driven policies and climate programs are needed to promote water management, a sustainable environment, early warning systems, and social safety net programs for pastoralists.